Literatur Review: Analisi Model Pembelajaran Blended Learning Dalam Pembelajaran IPA di Sekolah Dasar - Sijabat, Apriani; Juanta, Palma; Festiyed; Yerimadesi (Jurnal Elementaria Edukasia, 2023)
The purpose of writing this article is to provide an overview of the learning process of blended learning and studies that examine the effect of blended learning models on learning outcomes. Where this can be used as a reference in the use of blended learning models in learning science. The method used is the method of meta-analysis which was carried out through studies in a number of international and national journals in the last 3 years. Sampling using a homogeneous sampling strategy. The samples in this study were 30 international and national journals that discussed the blended learning model, which in this case focused more on the effect of the blended learning model on student learning outcomes. Data were obtained using the results summary instrument and data analysis. The results of the research show that from several studies reviewed in the last 3 years, it is stated that the blended learning model is generally effective in improving student learning outcomes, especially in learning Natural Sciences. Therefore this blended learning model can be used as a learning model that can be used in science lessons at school.